2019
DOI: 10.5755/j01.ee.30.2.21589
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Theory of Planned Behaviour Model for Examining Customers’ Intentions towards Islamic Hire Purchase Financing

Abstract: The paper deals with the issues relevant to behavioural economics studies, demonstrating psychological and behavioural aspects of Muslim banking customers across the world. The aim of the research is to investigate the factors that are significant to customers using the Islamic hire purchase (auto financing) in Pakistan. The novelty of this study is to develop a modified model based on the Theory of Planned Behaviour (TPB) and apply it to bridge this gap as well as to identify the determinants. The TPB model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Table displays the tolerated ranges of Cronbach's alpha and composite reliabilities are more than 0.85; however, according to Hair Jr. et al (), the threshold value is 0.60. Moreover, factor loadings of constructs are in the ranges of 0.80–0.95; hence, it also demonstrates that the criterion of discriminant validity is met (Ahmed et al, ). According to Fornell and Larcker (), the average variance extracted (AVE) values are more than 0.50 that also substantiated the convergent validities.…”
Section: Results Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…Table displays the tolerated ranges of Cronbach's alpha and composite reliabilities are more than 0.85; however, according to Hair Jr. et al (), the threshold value is 0.60. Moreover, factor loadings of constructs are in the ranges of 0.80–0.95; hence, it also demonstrates that the criterion of discriminant validity is met (Ahmed et al, ). According to Fornell and Larcker (), the average variance extracted (AVE) values are more than 0.50 that also substantiated the convergent validities.…”
Section: Results Analysismentioning
confidence: 94%
“…According to Ahmed et al (), it is a pre‐requisite that data should follow a normal pattern for the employment of structural equation modeling (SEM)‐based multivariate methods. Thus, data were converted into z‐scores, and descriptive analysis was then done.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of Table 1 confirm the normality pattern of the data; for this purpose, we transformed data into zscores and employed the descriptive analysis. The results demonstrated that values of skewness and standard deviation lie between ±1.5, and values of kurtosis range between ±3; hence, the normality of the collected data is evident (Ahmed et al, 2019;Byrne, 2013).…”
Section: Descriptive Analysismentioning
confidence: 90%
“…The outcomes of Table 2 exhibit that measure of composite reliabilities and Cronbach's alpha are more than 0.80, which meets the minimum criterion of 0.60 (Ahmed et al, 2019;Hair et al, 2010). The values of all the factors loadings (FL) that have been extracted through the rotated component matrix (Principal component analysis) are more than 0.50, which also meets the criterion of discriminant validities.…”
Section: Reliabilities and Ave Analysismentioning
confidence: 94%